Luminescence imaging of leaf damage induced by lipid peroxidation products and its modulation by β‐cyclocitral. Issue 2 (1st December 2020) - Rac, Marek; Shumbe, Leonard; Oger, Camille; Guy, Alexandre; Vigor, Claire; Ksas, Brigitte; Durand, Thierry; Havaux, Michel
Abstract: Lipid peroxidation is a primary event associated with oxidative stress in plants. This phenomenon secondarily generates bioactive and/or toxic compounds such as reactive carbonyl species (RCS), phytoprostanes, and phytofurans, as confirmed here in Arabidopsis plants exposed to photo‐oxidative stress conditions. We analyzed the effects of exogenous applications of secondary lipid oxidation products on Arabidopsis plants by luminescence techniques. Oxidative damage to attached leaves was measured by autoluminescence imaging, using a highly sensitive CCD camera, and the activity of the detoxification pathway, dependent on the transcription regulator SCARECROW‐LIKE 14 (SCL14), was monitored with a bioluminescent line expressing the firefly LUCIFERASE ( LUC ) gene under the control of the ALKENAL REDUCTASE ( AER ) gene promoter. We identified 4‐hydroxynonenal (HNE), and to a lesser extent 4‐hydroxyhexenal (HHE), as highly reactive compounds that are harmful to leaves and can trigger AER gene expression, contrary to other RCS (pentenal, hexenal) and to isoprostanoids. Although the levels of HNE and other RCS were enhanced in the SCL14‐deficient mutant ( scl14 ), exogenously applied HNE was similarly damaging to this mutant, its wild‐type parent and a SCL14‐overexpressing transgenic line (OE:SCL14). However, strongly boosting the SCL14 detoxification pathway and AER expression by a pre‐treatment of OE:SCL14 with the signaling apocarotenoid β‐cyclocitral canceled the damaging effects of HNE. Conversely, in the scl14 mutant, the effects of β‐cyclocitral and HNE were additive, leading to enhanced leaf damage. These results indicate that the cellular detoxification pathway induced by the low‐toxicity β‐cyclocitral targets highly toxic compounds produced during lipid peroxidation, reminiscent of a safener‐type mode of action.